(untitled) (REMUNOM, 2025)
Beverage production has represented a major advance in contemporary times, especially with economic importance in terms of consumption. Pharmacists are prominent professionals in this process, since one of their areas of activity is in the food and beverage industry, where they work in different stages and sectors, such as quality control and assurance. The objective of this study is to report on the importance of pharmacists in the beer production process, in addition to their role in quality assurance. It was developed through an integrative literature review, with a qualitative approach. For this study, the following databases will be consulted: National Center for Biotechnology Information (PUBMED), Scientific Electronic Library Online (SCIELO) and Latin American and Caribbean Literature in Health Sciences (LILACS). The following descriptors and their combinations in Portuguese and English were used to search for articles: “Beer production”; “pharmacist”; “Quality assurance”. Initially, the search for descriptors was carried out individually, in which all are registered. Scientific articles that underwent peer review, were original, in Portuguese and English, from 2016 onwards. The results were based on a critical analysis of the articles, focusing on understanding the importance of the pharmacist in the beer production process and in quality assurance, highlighting as the main result the attributions and flows necessary for pharmaceutical performance. It is concluded that performing quality control is essential to ensure and verify whether beer production meets the required quality standards through safe evaluation in all protocols established by the various regulatory agencies.